Evaluation of cortical thickness and cortical thickness index in the proximal femur-CT, dual energy absorptiometry (DXA), trabecular bone score (TBS). - Xiao Ma; Ik Yang; Sewon Lee; Jungyoun Kim; Hyunjin Park; Younghyun Yoon; Jihyo Hwang (PLoS ONE)
Purpose The purpose of this study was to assess the anatomical size of proximal femur in South Korea. This study measured cortical thickness and cortical thickness index (CTI) based on computed tomography (CT) and additionally, evaluated the T-score and trabecular bone score (TBS) based on the dual energy X-ray absorptiometry (DXA). Materials and methods This retrospective study is a cross-sectional study based on data from 600 patients aged from 20 to 93 years during the time from 2011 to 2021 were enrolled and selected the patients who did the examination of both pelvic CT and DXA scan. Age, sex, BMI, T-score, TBS, cortical thickness, CTI and the size of proximal femur were analyzed. Among these patients, 200 patients each corresponding to femoral neck fracture group(N = 200), trochanteric fracture group(N = 200), and non-fracture group(N = 200) were randomly selected and studied. The differences of three groups were compared statistically. Results Mean outer diameter of proximal femur was 24.34 mm, inner diameter of proximal femur was 15.28 mm, cortical thickness was 4.55 mm and CTI was 0.37 at the lesser trochanter (LT) level. The outer diameter was 24.00 mm, inner diameter of proximal femur was 13.04 mm, cortical thickness was 4.97mm and CTI was 0.44 at 3cm below LT. In the hip fracture group, T-score of hip, outer diameter of proximal femur and cortical thickness at LT were lower than non-fracture group. BMI, T-score of spine, T-score of hip, inner diameter at 3cm below LT, CTI of LT and TBS were lower in femoral neck fracture group compared to the trochanteric fracture group. Conclusion Analysis of 600 patients of pelvic CT might be a representative of real size of proximal femur in South Korea. Outer diameter of proximal femur at LT and cortical thickness at LT level were significantly lower in hip fracture group. Narrower outer diameter of proximal femur and thinner cortical thickness at LT level from the CT might be a risk factor of hip fracture.